2013
DOI: 10.1152/ajplung.00352.2012
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of inflammatory mediator production by the NF-κB member RelB is mediated by microRNA-146a in lung fibroblasts

Abstract: Lung inflammation can result from exposure to multiple types of inflammatory stimuli. Fibroblasts, key structural cells in the lung that are integral to inflammation and wound healing, produce inflammatory mediators after exposure to stimuli such as IL-1β. We and others have shown that the NF-κB member RelB has anti-inflammatory properties in mice. Little is known, however, about the anti-inflammatory role of RelB in human cells and how it functions. MicroRNAs (miRNAs), a novel class of small, noncoding RNAs, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 48 publications
(76 reference statements)
1
16
0
Order By: Relevance
“…This data indicated that AP1 is the key transcription factor contributing to EV71-induced upregulation of miR-146a. Previous studies have reported that RelA, RelB and p50 could regulate miR-146a expression and suggested that miR-146a expression was NF-kB-dependent 32,[39][40][41][42] . To verify whether NF-kB is involved in EV71-induced miR-146a upregulation, NF-kB translocation and NF-kB activity were examined in EV71-infected RD cells and assayed by NF-kB immunoblot and NF-kB regulatory element assays.…”
Section: Resultsmentioning
confidence: 98%
“…This data indicated that AP1 is the key transcription factor contributing to EV71-induced upregulation of miR-146a. Previous studies have reported that RelA, RelB and p50 could regulate miR-146a expression and suggested that miR-146a expression was NF-kB-dependent 32,[39][40][41][42] . To verify whether NF-kB is involved in EV71-induced miR-146a upregulation, NF-kB translocation and NF-kB activity were examined in EV71-infected RD cells and assayed by NF-kB immunoblot and NF-kB regulatory element assays.…”
Section: Resultsmentioning
confidence: 98%
“…miR27 is primarily linked to adipocyte differentiation, with increased miR27a decreasing adipogenesis, but has additionally been shown to be downregulated by TLR4 induction, resulting in reduced IL-10, an anti-inflammatory cytokine important in M2 macrophage activation (58). miR-146a is both regulated by and negatively regulates TLR4, MyD88, NF-kB, other TLRs, and a range of proinflammatory proteins, as well positively regulating RelB (37,(59)(60)(61)(62)(63)(64). The effects of regulation have been specifically identified in macrophages; THP-1 cells that are exogenously transfected with a miR-146a mimic had decreased production of TNF-a, IL-6, and IL-1b (62).…”
Section: Vol 30 September 2016mentioning
confidence: 99%
“…We and others have shown that RelB expression is increased by IL-1b stimulation (data not shown and (Vardar-Sengul et al, 2009;McMillan et al, 2013)). McMillan et al demonstrated that RelB reduces inflammatory mediator production, in part, via a miRNA dependent mechanism, and showed that RelB and miR-146a may coordinately regulate this anti-inflammatory pathway (McMillan et al, 2013). In human lung fibroblasts depleted of RelB, overexpression of miR-146a reversed the RelB downregulation-induced increase in IL-1b inflammatory mediator production (IL-6, IL-8 and MCP-1).…”
Section: Discussionmentioning
confidence: 64%
“…Another possible explanation for how mapracorat could regulate RelB involves a recently reported novel feedback control mechanism in human lung fibroblasts that functions to reduce and reverse the prolonged effects of inflammation (McMillan et al, 2013). We and others have shown that RelB expression is increased by IL-1b stimulation (data not shown and (Vardar-Sengul et al, 2009;McMillan et al, 2013)).…”
Section: Discussionmentioning
confidence: 83%